2006
DOI: 10.3402/ijch.v65i1.17884
|View full text |Cite
|
Sign up to set email alerts
|

Dental health status and development trends among children and adolescents in Greenland

Abstract: Objectives. This paper describes the occurrence of dental caries in children and adolescents in Greenland and the disease pattern is analysed across districts and over time. Study design. Cross-sectional population surveys of children aged 6, 12 and 15 years. Methods. Data were stored in the oral health information system established for the Greenland Public Dental Health Services, recording the dental health status of children served by the programme. The participation rate is approximately 100%. In 2003, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Yet the prevalence of caries in this study of 57.1% is much lower than was reported 10 years earlier. In 2005, Petersen and Christensen found the caries prevalence rate among Greenlandic children to be as high as 80–90% [27], which is comparable to the Canadian Inuit community, where over 85% of pre-schoolers in 2008–2009 were found to have caries [28]. A recent study from 2015 found positive effects on caries prevalence among 3- and 9-year-old children after implementation of the National Caries Strategy in Greenland in 2007 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Yet the prevalence of caries in this study of 57.1% is much lower than was reported 10 years earlier. In 2005, Petersen and Christensen found the caries prevalence rate among Greenlandic children to be as high as 80–90% [27], which is comparable to the Canadian Inuit community, where over 85% of pre-schoolers in 2008–2009 were found to have caries [28]. A recent study from 2015 found positive effects on caries prevalence among 3- and 9-year-old children after implementation of the National Caries Strategy in Greenland in 2007 [9].…”
Section: Discussionmentioning
confidence: 99%
“…T he use of fluoride is the main reason for the decrease in prevalence of caries seen lately in Western industrialized countries (Bratthall, 2005;Petersen and Christensen, 2006;Pitts et al, 2006). Otherwise, recent surveys have described a reversal of this trend: a small but significant increase in caries prevalence was detected in primary and permanent dentition (Bagramian et al, 2009).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Furthermore, restorative – as opposed to preventive – dental care was dominant. The activities have resulted in a constant but small improvement in the caries experience among adolescents in Greenland, i.e., the mean DMFS index for 15‐year‐olds was 10.6 in 1996, 10.0 in 2002, and 9.2 in 2008 compared to 4.1 (1996), 3.1 (2002), and 2.3 (2008) in Denmark.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the very high caries experience in the Greenlandic population, it has several times be discussed to add fluoride artificially to the water supply on a national scale. There is, however, no central water supply system in Greenland, and it was finally concluded that such a community‐based approach is not feasible in Greenland. The implementation of salt fluoridation in Greenland, as decided upon by the home rule cabinet in 2005 following the recommendation of WHO, was supposed to compensate for the lack of natural fluoride in the water supply.…”
Section: Discussionmentioning
confidence: 99%